Critical Thinking: Importance, Development Strategies, Characteristics, and Limiting Factors - Salomón Vásquez Villanueva; Juan Félix Quispe-Gonzales; Gezel Raquel Vásquez-Jiménez; Salomón Axel Vásquez Campos; Julissa Torres Acurio; Ruth Vallejos-Atalaya (My University, 2021)
Critical thinking is a topic that is not excluded from academic spaces and research, its approach will always be valid. In this study, it is approached with the objective of analyzing its importance, development strategies, characteristics and limiting factors. In order to achieve the objective, a theoretical review on critical thinking has been carried out, resorting to processes of analysis, synthesis and conclusions, allowing them to be argued, coherent and consistent. Finally, it has been concluded that critical thinking has a relevant importance for students, whose development is achieved through the use of didactic strategies, observing that its characteristics are unique, without leaving aside the presence of the factors that limit it.
Keywords: Limiting; Aside; Critical thinking; Limit (mathematics); Development (topology); Management science; Order (exchange); Epistemology; Computer science; Engineering ethics; Risk analysis (engineering); Psychology; Mathematics education; Mathematics; Engineering; Economics; Business; Philosophy; Finance; Mathematical analysis; Mechanical engineering; Linguistics; Limiting; Aside; Critical thinking; Limit (mathematics); Development (topology); Management science; Order (exchange); Epistemology; Computer science; Engineering ethics; Risk analysis (engineering); Psychology; Mathematics education; Mathematics; Engineering; Economics; Business; Philosophy; Social Sciences Social Sciences Education Education and Teacher Training; Social Sciences Social Sciences Safety Research Social impacts of COVID-19; Physical Sciences Computer Science Information Systems Educational Innovations and Technology